Penguatan Hak Narapidana Dan Anak Di Masa Pandemi Covid-19 Dalam Perspektif Hak Asasi Manusia - Ridwan, Mukhlis (JURNAL USM LAW REVIEW, 2022)
This study aims to examine the implementation of the rights of prisoners and children and the obstacles faced in the implementation of the fulfillment of the rights of prisoners and children in prisons during the Covid-19 pandemic. The rights of prisoners and children as stated in Law Number 12 of 1995 concerning Corrections are human rights. The implementation of the fulfillment of the rights of prisoners and children in correctional institutions has not been maximized, and during the Covid-19 pandemic, it is increasingly difficult to implement. There are obstacles faced, therefore it is necessary to strengthen for the future in the form of synergies with all government and public components. The research method used in this research is sociological juridical. Correctional institutions must have programs that are oriented towards the fulfillment of the rights of prisoners and children. The need for reforming the bureaucracy and recruiting human resources according to the required qualifications. Then the most important thing is independence, including the role model of correctional officers in carrying out their main duties and functions and eliminating all forms of intervention that can affect the implementation of the coaching process in an effort to fulfill the rights of prisoners and criminal children in correctional institutions and child correctional institutions.Penelitian ini bertujuan mengkaji pelaksanaan hak-hak narapidana dan anak beserta kendala yang dihadapi dalam pelaksanaan pemenuhan hak narapidana dan anak di lembaga pemasyarakatan pada masa pandemi Covid-19. Hak-hak narapidana dan anak yang telah disebutkan dalam Undang-Undang Nomor 12 Tahun 1995 tentang Pemasyarakatan adalah hak asasi manusia. Pelaksanaan pemenuhan hak narapidana dan anak di Lapas belum maksimal, dan pada masa pandemi Covid-19 semakin sulit terlaksana. Terdapat kendala yang dihadapi, maka perlu penguatan untuk masa yang akan datang berupa sinergi bersama semua komponen pemerintah dan masyarakat. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis sosiologis. Lembaga pemasyarakatan harus mempunyai program yang berorientasi pada pemenuhan hak-hak narapidana dan anak. Perlunya pembenahan birokrasi dan rekrutmen sumber daya manusia sesuai kualifikasi yang dibutuhkan. Kemudian yang paling penting independensi, termasuk ketauladanan para pegawai lembaga pemasyarakatan dalam menjalankan tugas pokok dan fungsi, serta menghilangkan segala bentuk intervensi yang dapat mempengaruhi terlaksananya proses pembinaan dalam upaya pemenuhan hak-hak narapidana dan anak pidana di lembaga pemasyarakatan dan lembaga pemasyarakatan khsusus anak.